If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 65 = 6x + 9 Reorder the terms: 65 + 2x = 6x + 9 Reorder the terms: 65 + 2x = 9 + 6x Solving 65 + 2x = 9 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 65 + 2x + -6x = 9 + 6x + -6x Combine like terms: 2x + -6x = -4x 65 + -4x = 9 + 6x + -6x Combine like terms: 6x + -6x = 0 65 + -4x = 9 + 0 65 + -4x = 9 Add '-65' to each side of the equation. 65 + -65 + -4x = 9 + -65 Combine like terms: 65 + -65 = 0 0 + -4x = 9 + -65 -4x = 9 + -65 Combine like terms: 9 + -65 = -56 -4x = -56 Divide each side by '-4'. x = 14 Simplifying x = 14
| 3x-24=x+4 | | -7.3-5.18=-51.9 | | 4(4w+5)+3w=8(w+7)-3 | | 3x^3-51x=0 | | 20c=183 | | 22=2(4a+2) | | 20c=89 | | 5x+3-2x+11=x-6+x+14 | | 183w=4 | | -3x+1=-26 | | x^4-6x^2=-4 | | 4c=89 | | -3(7-2y)=-14-1 | | .05x+10(200-x)=.45x | | (x^4)+(-10x^2)+(16)=0 | | 2(y-3)=4x | | -1(8m+4)=4m-2(6m+2) | | -2x+7=2 | | (x^4)-(12x^2)+(11)=0 | | 0.5y+1=4x-2 | | 2x-5y=28 | | -5(x+4)=7-(-5) | | (3+2i)(4+3i)= | | -3x+8=2x+3 | | (3/y)+(2/5)=19/20 | | 6x^2+4x=21 | | -7(2x+8)=14 | | 8z+22=3(3z+11)z | | 11x-3x=400 | | (x^4)-(5x^2)+(4)=0 | | 6(2/3x-7/6)=6*7/2 | | -2y-1=4x+3 |